Pendekatan Kasih Sayang dalam Pembentukan Karakter Pada Anak Usia Dini Perspektif Hadits Nabi Muhammad SAW - Rambe, Anggi Afrina; Udin Supriadi; Mokh. Iman Firmansyah; Regita Ayu Dwietama; Annisa Ningtias Cevie Putri; Muhammad Nurfaizi Arya Rahardja; Junaidi Marbun (Institut Agama Islam Negeri Madura, 2024)
This study aims to analyze and explore the meekness approach in character building in early childhood based on the perspective of Muslim hadith number 2935. This hadith emphasizes the importance of gentleness in social interactions and confirms that Allah SWT loves gentleness and provides special rewards for people who are gentle. Therefore, this study examines the meek approach as an alternative in character building in early childhood. The method used in this research is a literature study that involves the collection and analysis of various relevant literature sources, which include books, hadith books, journals and scientific articles that refer to the same topic. The results show that the gentle approach is very effective in shaping character in early childhood. Principles such as empathy, positive communication, tolerance, compassion and care are also contained in the character building. Through the role of parents and teachers, character in early childhood can be formed by applying a gentle approach as taught in Muslim hadith number 2935 which has a positive impact on the formation of children's character. Furthermore, this gentle approach makes children able to understand the surrounding environment and can manage themselves not to be rude, so that social relationships are created in harmony and affection.